Modeling bacterial microcompartment architectures for enhanced cyanobacterial carbon fixation - Trettel, Daniel S.; Pacheco, Sara L.; Laskie, Asa K.; Gonzalez-Esquer, C. Raul (Frontiers in Plant Science, 2024)
The carboxysome is a bacterial microcompartment (BMC) which plays a central role in the cyanobacterial CO2-concentrating mechanism. These proteinaceous structures consist of an outer protein shell that partitions Rubisco and carbonic anhydrase from the rest of the cytosol, thereby providing a favorable microenvironment that enhances carbon fixation. Their functional capacity to segregate metabolismThe modular nature of carboxysomal architectures makes them attractive for a variety of biotechnological applications such as carbon capture and utilization. However, carboxysomes are difficult to study and engineer due to their structural complexity. The implementation of computational approaches, like In silico approaches, such as molecular dynamics (MD) simulations, can support future carboxysome redesign efforts by providing new spatiotemporal insights on their structure and function beyond to complement in vivo experimental limitations. However, increasingly provide new spatio-temporal insights on BMC structure and function, but specific computational studies on carboxysomes are limited. However, all BMC (including the carboxysome) are highly structurally conserved which allows for practical inferences to be made between classes. Here, we review MD findingssimulations on BMC architectures which shed light on (1) permeation events through the shell and (2) assembly pathways.. These models predict the biophysical properties surrounding the central pore in BMC-H shell subunits, which in turn dictate the efficiency of substrate diffusion. Meanwhile, simulations on BMC assembly demonstrate that assembly pathway is largely dictated kinetically by cargo interactions while final morphology is dependent on shell factors. Overall, these findings are contextualized within the wider experimental BMC literature and framed within the opportunities for carboxysome redesign for biomanufacturing and enhanced carbon fixation.